2022
DOI: 10.7554/elife.82810
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effects of Ksr2, an obesity gene, on trabecular bone volume and bone marrow adiposity

Abstract: Pathological obesity and its complications are associated with an increased propensity for bone fractures. Humans with certain genetic polymorphisms at the kinase suppressor of ras2 (KSR2) locus develop severe early-onset obesity and type 2 diabetes. Both conditions are phenocopied in mice with Ksr2 deleted, but whether this affects bone health remains unknown. Here we studied the bones of global Ksr2 null mice and found that Ksr2 negatively regulates femoral, but not vertebral, bone mass in two genetic backgr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…KSR1 is the dominant protein expressed rather than KSR2 which is one of the reasons this genetic mouse model is useful for studying the role of the MAPK pathway in hearing loss. Both proteins can act as scaffolding proteins in the MAPK pathway, but they can have different physiological functions ( Gomez et al, 2022 ; Paniagua et al, 2022 ). KSR1 was hypothesized to play more of a role in hearing loss than the KSR2 protein due to KSR1 having much higher expression in the inner ear and being required for optimal MAPK signaling.…”
Section: Discussionmentioning
confidence: 99%
“…KSR1 is the dominant protein expressed rather than KSR2 which is one of the reasons this genetic mouse model is useful for studying the role of the MAPK pathway in hearing loss. Both proteins can act as scaffolding proteins in the MAPK pathway, but they can have different physiological functions ( Gomez et al, 2022 ; Paniagua et al, 2022 ). KSR1 was hypothesized to play more of a role in hearing loss than the KSR2 protein due to KSR1 having much higher expression in the inner ear and being required for optimal MAPK signaling.…”
Section: Discussionmentioning
confidence: 99%
“…KSR1 is the dominate isoform expressed rather than KSR2 which is one of the reasons this genetic mouse model is useful for studying the role of the MAPK pathway in hearing loss. Both isoforms can act as scaffolding proteins in the MAPK pathway, but they can have different physiological functions 28,29 . KSR1 was hypothesized to play more of a role in hearing loss than the KSR2 isoform due to KSR1 having much higher expression in the inner ear and being required for optimal MAPK signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we speculated that folic acid intake may affect total BMD, thereby affecting bone health. The previous study found that body fat is closely related to bone health, 27,28 but it is still unclear whether the effect of folic acid on BMD is directly caused or mediated by body fat. Therefore, we analyzed the body fat rate as an intermediary factor of folic acid on BMD, and the mediating effect accounted for 82.7% of the total effect (Fig.…”
Section: The Association Between Folic Acid Intake and Total Bmd May ...mentioning
confidence: 99%